Application of polydimethylsiloxane-based optical system for measuring optical density of microbial culture. Issue 12 (1st December 2016) - Takahashi, Yurika
Abstract: The performance of recently developed polydimethylsiloxane (PDMS)-based optical system was tested for measuring optical density of microbial culture. The data showed that PDMS-based spectrometer is superior to "one drop" spectrometers in the accuracy, and has an advantage over conventional spectrometers in measuring dense culture without dilution.